1993
DOI: 10.1159/000147518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Phenobarbital Consumption on Muscle Development in Mice

Abstract: The effect of prenatal exposure to phenobarbital on muscle development was determined in 4 muscles (biceps brachii, triceps brachii, soleus and cranial tibial) of 34 mice (16 males, 18 females) at 12 weeks of age. The control group received unadulterated food ad libitum throughout the period of study. The phenobarbital-exposed group received 3 g of phenobarbital per kilogram of food from gestation day 7 to 18 as the only source of food. Outside this period they received unadulterated food and water ad libitum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
6
4
0
Order By: Relevance
“…It is also similar to what was described as lack of catch-up growth in FAS in humans [Hanson et al, 1976] and experimental animals [Abel and Dintcheff, 1978;Leichter and Lee, 1979]. The lack of catch-up growth as observed in the muscles postnatally may be due to the fact that the number of muscle fibres is fixed prenatally or shortly after birth [Rowe and Goldspink, 1969;Goldspink, 1972], since Ihemelandu [1984] reported a loss of muscle fibres and no differences in muscle fibre sizes in mice exposed to alcohol prenatally. The results of this study have also established that maternal alcohol consumption in rats during prenatal and postnatal periods produced retardation of growth and lack of catch-up growth of the offspring.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is also similar to what was described as lack of catch-up growth in FAS in humans [Hanson et al, 1976] and experimental animals [Abel and Dintcheff, 1978;Leichter and Lee, 1979]. The lack of catch-up growth as observed in the muscles postnatally may be due to the fact that the number of muscle fibres is fixed prenatally or shortly after birth [Rowe and Goldspink, 1969;Goldspink, 1972], since Ihemelandu [1984] reported a loss of muscle fibres and no differences in muscle fibre sizes in mice exposed to alcohol prenatally. The results of this study have also established that maternal alcohol consumption in rats during prenatal and postnatal periods produced retardation of growth and lack of catch-up growth of the offspring.…”
Section: Discussionsupporting
confidence: 77%
“…This is evident when the absolute muscle weights as well as percentage of body weight contributed by these muscles were used as indices of growth since the weight of any muscle is influenced by the weight of the body [Joubert, 1956]. This observation is similar to the findings of Ihemelandu [1984]. It is also similar to what was described as lack of catch-up growth in FAS in humans [Hanson et al, 1976] and experimental animals [Abel and Dintcheff, 1978;Leichter and Lee, 1979].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This observation is similar to the findings of Taylor et al (1981) and Onu et al (2002a) on testicular growth in fetal alcohol syndrome in rat. The observation also agrees with what was described as lack of catch-up growth in fetal alcohol syndrome in humans (Hanson et al, 1976) and in experimental animals (Lee and Leichter, 1980;Ihemelandu, 1984). However, the results of this study also revealed that the epididymis exposed to alcohol during pregnancy and during pregnancy and lactation attempted to catch-up growth with their control counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of maternal alcohol intake on the growth and development of some parts of the body in both human and experimental animals have been reported (Lee and Leichter, 1980;Ihemelandu, 1984;Clarren et al, 1985;Piqueras-Renau et al, 1987;Nwaogu and Ihemelandu, 1999a, b). In the reproductive system, reduced growth have been reported on the testes (Onu and Ezeasor, 2001;Onu et al, 2002a, b;Fakoya and Caxton-Martins, 2004) and on the penis (Onu et al, 2004).…”
mentioning
confidence: 99%